2008
DOI: 10.1177/1078390307311770
|View full text |Cite
|
Sign up to set email alerts
|

Parent—Adolescent Communication About Sexual Pressure, Maternal Norms About Relationship Power, and STI/HIV Protective Behaviors of Minority Urban Girls

Abstract: Racial/ethnic minority adolescent girls bear a disproportionate risk for HIV and face barriers to autonomous sexual decision making, but parental messages may help protect against sexual risk taking. The authors examined African American and Hispanic girls' sexually transmitted infection (STI) and HIV prevention practices, parent-adolescent communication about sexual pressure, and maternal gender norms (N = 118). Teens were more likely to practice consistent STI/HIV prevention when mothers talked about partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 32 publications
4
33
0
1
Order By: Relevance
“…Similar to reports of other scholars [41,42], our study found that topic-specific communication is more effective and more preferred compared with global forms of communication.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to reports of other scholars [41,42], our study found that topic-specific communication is more effective and more preferred compared with global forms of communication.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, because we hypothesized that the effects of partner pressure, victimization history severity, and their interaction would be different in alcohol and control groups, we allowed these paths to vary freely. The hypothesized model was not a good fit for the data: χ 2 (10) = 27.89, p = .002; RMSEA (root mean square error of approximation) = .094 (90% confidence interval = .054, .136); CFI (comparative fit index) = .887; TLI (Tucker-Lewis index) = .594; SRMR (standardized root mean squared residual) = .048. Based on modification indices, we added a free direct path from the partner pressure by victimization history severity interaction to the abdication intention outcome (along with the victimization history severity to condom-decision abdication intention path necessary to test this interaction).…”
Section: Resultsmentioning
confidence: 93%
“…For example, Teitelman, Ratcliffe, & Cederbaum (10) described sexual pressure as a form of social influence “toward having sex or having sex in a particular way (e.g., without condoms).” Similarly, Jones (11) conceptualized and operationalized sexual pressure as an internalized construct reflecting a woman’s gender stereotypical concerns about adverse consequences resulting from not meeting a man’s expectations for sex; again placing the emphasis on coercive pressure for sex generally. Although valuable for documenting women’s subjective sense of feeling pressured to have sex, such research provides little illumination about men’s pressure for unprotected sex with women who are willing to consent to protected sex and the role such pressure plays in their eventual risk decision.…”
Section: Partner Pressure For Unprotected Sexmentioning
confidence: 99%
“…It is encouraging to see that both mothers and fathers believed that they would communicate with their children about some of these sexuality topics. Research shows that when parents communicate with their child, the child is more likely to have positive self-efficacy, later age of sexual initiation, use contraception, have greater negotiation skills, and communicate with partners (Crosby et al, 2009;DiClemente et al, 2001;Hadley et al, 2009;Hutchinson, 2002;Hutchinson, Jemmott, Jemmott, Braverman, & Fong, 2003;Jerman & Constantine, 2010;Kapungu et al, 2010;Teitelman, Ratcliffe, & Cederbaum, 2008). While the NSES were developed for schools to outline the minimal essential content to teach in K-12th grades, these standards could also be used as a guide for parents.…”
Section: Sexuality Education Discussed At Homementioning
confidence: 98%